High dams on the Narmada : a holistic analysis of the river valley projects - "Paranjpye, Vijay" (New Delhi, 1990)
This book contains following topics: The cultural ethos; History of the development projects; The Narmada water Disputes Tribunal Award; The economics of dams in India; Gujarat: the economic setting and the development of irrigation; Economic analysis of the Sardar Sarovar Project; Resettlement and Rehabilitation; Madhya Pradesh: the economic setting ; The quest for alternatives; Summary of conclusion.
Keywords: Dams-Narmada